What geopolitical returns does ODA bring? - Nicolas Bau; Simone Dietrich (Kiel Institute for the World Economy, 2025)
We review the literature on the political economy of foreign aid, examining the geopolitical returns generated by Official Development Assistance (ODA). Our paper identifies conditions under which donors are able to influence political and economic outcomes in recipient countries, shape their behavior in global affairs, and adjust to domestic and international challenges. First, we introduce our paper and outline the structure of our review. Second, we examine how the international system influences foreign aid motivations. Third, we discuss the literature on aid-giving practices and their geopolitical effects. Fourth, we explore the relationship between aid and international organizations. Fifth, we identify key challenges to the traditional aid architecture. Sixth, building on an emerging body of research in international development finance, we propose future directions for the study of ODA in a contested global landscape. Finally, we conclude by summarizing the main insights from our review.
Keywords: F35; O19; P45; 330; foreign aid; geopolitics; foreign policy; development; international organizations; development finance; aid effectiveness